Postpartum panhypopituitarism (Sheehan syndrome). Study of eleven cases - Calderon Velasco, Rolando (2015)
Panhypopituitarism eleven cases of ischemic necrosis caused by postpartum, in which a study of the thyroid, adrenal and gonadal functions is presented. Gingival bleeding profusely and repetition is described in 5 of the 11 cases studied, a fact not mentioned in the literature reviewed. It has compiled the relevant references, and emphasized that the syndrome Sheehan, is not a rare disease entity once observed.